2012
DOI: 10.1186/1475-2859-11-141
|View full text |Cite
|
Sign up to set email alerts
|

“Direct cloning in Lactobacillus plantarum: Electroporation with non-methylated plasmid DNA enhances transformation efficiency and makes shuttle vectors obsolete”

Abstract: BackgroundLactic acid bacteria (LAB) play an important role in agricultural as well as industrial biotechnology. Development of improved LAB strains using e.g. library approaches is often limited by low transformation efficiencies wherefore one reason could be differences in the DNA methylation patterns between the Escherichia coli intermediate host for plasmid amplification and the final LAB host. In the present study, we examined the influence of DNA methylation on transformation efficiency in LAB and develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
50
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 45 publications
1
50
0
Order By: Relevance
“…The disadvantage of this product is that it is highly methylated. This methylated DNA inhibits the transformation efficiency via electroporation to lactic acid bacteria, the bacteria that was used to produce therapeutic recombinant proteins, by a factor of 1,000(23). Unfortunately, such a simple test has not been found in either cell culture or in vivo tissues in a mammalian system but remains a project worthy of attention.…”
Section: Effects Of Dna Properties On Dna Electroporationmentioning
confidence: 99%
See 2 more Smart Citations
“…The disadvantage of this product is that it is highly methylated. This methylated DNA inhibits the transformation efficiency via electroporation to lactic acid bacteria, the bacteria that was used to produce therapeutic recombinant proteins, by a factor of 1,000(23). Unfortunately, such a simple test has not been found in either cell culture or in vivo tissues in a mammalian system but remains a project worthy of attention.…”
Section: Effects Of Dna Properties On Dna Electroporationmentioning
confidence: 99%
“…It has been shown that the mechanisms for enhanced transformation via electroporation in lactic acid bacteria were eliminating methylation-specific restriction enzyme activity and reducing DNA degradation(23). This explanation cannot exclude the possibility of an increased level of gene expression from the unmethylated DNA.…”
Section: Effects Of Dna Properties On Dna Electroporationmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactobacillus plantarum CD033 is a lactic acid bacterium 39 (LAB) that was isolated from grass silage and was previously 40 characterized regarding its use as a possible expression host 41 (Spath et al, 2012a(Spath et al, ,2012b. The species L. plantarum belongs to 42 the mammalian oral-and gastrointestinal natural inhabitants 43 (Kleerebezem et al, 2003), is responsible for fermentation of 44 meat and milk products as well as for preservation of feed raw 45 material such as grass and cereal grains (Wanker et al, 1995;46 Siezen et al, 2010).…”
mentioning
confidence: 99%
“…Since LAB have a long history in food and Transformation of E. coli JM109 cells was carried out by 122 electroporation according to Sambrook and Russel (2001). 123 Transformation of L. plantarum was performed by electropora-124 tion as described elsewhere (Spath et al, 2012a). followed by overnight capillary blotting (Southern, 1975).…”
mentioning
confidence: 99%